Migrants With Schizophrenia in Forensic Psychiatric Hospitals Benefit From High-Intensity Second Language Programs - Lutz, Maximilian; Streb, Judith; Titze, Larissa; Büsselmann, Michael; Riemat, Nadja; Prüter-Schwarte, Christian; Dudeck, Manuela (Frontiers in Psychiatry, 2021)
Background: As a result of migration, an increasing number of patients in forensic psychiatric hospitals show poor skills in the national language, which can affect their treatment. Improving the second language (L2) of inpatients with schizophrenia may help to enable effective psychotherapy and thus reduce the risk of criminal recidivism and facilitate reintegration into society, for example because of a language-related higher degree of social functioning. For this purpose, a Hessian forensic psychiatric hospital established a ward specialized in L2 acquisition. The ward accommodates up to 21 patients with schizophrenia, who attend an L2 program consisting of 800–900 lessons within 1 year. Aims: The study aimed to evaluate whether patients on the specialized ward (experimental group) achieve at least Common European Framework of Reference (CEFR) level A2 in the L2 program. Additionally, it examined whether language acquisition is better among participants in the experimental group than among those on regular wards (control group). Methods: Achievements in the L2 were assessed by an L2 test 3 times: at the beginning of the program, after 6 months, and after 1 year. The impact of intelligence on achievements in L2 was evaluated using Raven's Standard Progressive Matrices. Results: The experimental group showed significantly better improvement than the control group. Literacy was a significant predictor of improvement in the L2. The majority of the experimental group reached at least CEFR level A2 after 1 year. Conclusions: High-intensity L2 programs are an effective way to improve the L2 of inpatients with schizophrenia in forensic psychiatric hospitals.